Age determination of glacially-transported boulders in Ireland and Scotland using Schmidt-hammer exposure-age dating (SHD) and terrestrial cosmogenic nuclide (TCN) exposure-age dating. Issue 2 (September 2019) - Wilson, Peter; Dunlop, Paul; Millar, Chris; Wilson, Frances A.
Abstract: Schmidt-hammer exposure-age dating (SHD) was applied at 15 sites with glacially-transported granite boulders in parts of northern and western Ireland and southwest Scotland that had been exposed by retreat of the last British-Irish Ice Sheet (BIIS) or Younger Dryas (YD) ice masses. Seven of these surfaces had previously been dated using terrestrial cosmogenic nuclide (TCN) exposure-age dating. Application of the granite calibration equation of Tomkins et al. (2018c) indicated a close correspondence between the SHD ages and the TCN ages (within 1σ or 2σ uncertainties). These findings demonstrate that SHD ages can be of comparable accuracy, precision, and reliability to TCN ages and are a strong argument for the more extensive use of SHD in some Quaternary dating projects. However, surface ages obtained by both SHD and TCN dating should not be accepted uncritically; they must be assessed in relation to the wider geological, geomorphological, and geochronological evidence. Evaluation of eight SHD ages, for which corresponding TCN ages are not available, indicate that most are consistent with current theory and field evidence, but some anomalous age estimates occur.